The Projection From Ventral CA1, Not Prefrontal Cortex, to Nucleus Accumbens Core Mediates Recent Memory Retrieval of Cocaine-Conditioned Place Preference - Zhou, Yiming; Yan, Enhui; Cheng, Deqin; Zhu, Huiwen; Liu, Zhiyuan; Chen, Xi; Ma, Lan; Liu, Xing (Frontiers in Behavioral Neuroscience, 2020)
Drug-paired cues inducing memory retrieval by expressing drug-seeking behaviors presents the major challenge to drug abstinence. How neural circuits coordinate for drug memory retrieval remains unclear. Here we report that exposure of the training chamber where cocaine-conditioned place preference (CPP) was performed increased neuronal activity in the core of nucleus accumbens (AcbC), ventral CA1 (vCA1), and medial prefrontal cortex (mPFC), as shown by elevated pERK and c-Fos levels. Chemogenetic inhibition of neuronal activity in the vCA1 and AcbC, but not mPFC, reduced the time spent in the cocaine-paired compartment, suggesting that the vCA1 and AcbC are required for retrieval of cocaine-CPP memory and are key nodes recruited for cocaine memory storage. Furthermore, chemogenetic inhibition of the AcbC-projecting vCA1 neurons, but not the AcbC-projecting mPFC neurons, decreased the expression of cocaine-CPP. Optogenetic inhibition of the vCA1-AcbC projection, but not the mPFC-AcbC projection, also reduced preference for the cocaine-paired compartment. Taken together, the cue-induced natural recall of cocaine memory depends on vCA1-AcbC circuits. The connectivity from the vCA1 to the AcbC may store the information of the cue-cocaine reward association critically required for memory retrieval. These data thus provide insights into the neural circuit basis of retrieval of drug-related memory.